Sleep Disorders in Adolescents : A Clinical Casebook - Kothare, Sanjeev V.; Quattrucci Scott, Rebecca (Springer International Publishing : Imprint: Springer, 2017)
This clinical casebook presents a comprehensive review of common sleep problems in adolescents in a concise, easy-to-read format. Each chapter thoroughly addresses a unique sleep disorder in teenagers through illustrative cases, reviews of relevant literature, and pearls of wisdom for both the practicing sleep specialist and other practitioners involved in the care of adolescents. Early chapters address various sleep disorders in detail: parasomnias, narcolepsy, obstructive sleep apnea, and delayed sleep-wake phase disorder, providing clear treatment considerations. Later chapters address sleep when complicated by issues of major depression, PTSD, epilepsy, and Traumatic Brain Injury. In-depth discussions and differential diagnosis engage the reader, and offer a multitude of research-based and clinically guided recommendations for the evaluation and treatment of sleep disorders in the adolescent. An ideal, practical resource for clinicians at all levels,.
Keywords: Medicine.; General practice (Medicine).; Internal medicine.; Neurology.; elektronické knihy; electronic books